Pengaruh Penggunaan Media Pembelajaran Trainer Kelistrikan Body Terhadap Motivasi Belajar dan Hasil Belajar - Pratiwi, Monica; Sufarinto, Adhitya (Universitas Negeri Gorontalo, 2024)
This research aims to provide information about the importance of using learning media in the form of body electrical trainers in increasing motivation and optimal learning outcomes in the field of education. The method used in this research is Expost Facto, namely research that examines events that have occurred and then traces them back to find out the factors that contributed to the incident. The research results show that there is a very strong relationship between learning media and student learning motivation and a very strong relationship between learning media and student learning outcomes. The contribution of learning media variables to learning motivation calculated using the KP formula is 90.4%. Based on the data analysis, it can be concluded that H0 is rejected and Ha is accepted so that learning media has an effect on the learning motivation of Mechanical Engineering Education students by 90.4%. Apart from that, the contribution of learning media variables to learning outcomes which is also calculated using the KP formula is 72.7%. From the data analysis, it can be concluded that H0 is rejected and Ha is accepted, indicating that learning media has an effect on the learning outcomes of Mechanical Engineering Education students by 72.7%.